Peranan Wanita dalam Penyelesaian Konflik di Selatan Filipina: The Role of Women in Conflict Resolution at the Southern Philippines - Kadir, Norizan Binti (Journal of Al-Tamaddun, 2021)
The roles played by the women in the conflict resolution involving the Muslim community in the Southern Philippines was not given the spotlight it deserved in the series of peace talks between the republic and the separatist groups. The roles of women were as if they were insignificant and of a passive manner while women were undeniably the important “stakeholder” beside the fact that the conflict that erupted affected this group the most amongst the population there. They are also capable to contribute to a new paradigm in conflict resolution. Realizing this, the United Nations Security Council Resolution (UNSCR) passed Resolution 1325 on Women, Peace and Security as a democratizing mechanism towards the encouragement of women in conflict resolution, protection amidst conflict, and peacemaking.